Oil sector development strategies and processes in the Republic of Kazakhstan - Mussina, T.A. (Ye.A.Buketov Karaganda State University Publ., 2014)
In the 21st century with growing demands of oil and gas worldwide, one can observe the rising interest in resource- rich countries in Caucasian and Central Asian regions. The possession of vast natural resources and major powers' interests in it do not always guarantee successful development for a country but in some cases they have an influence on its future. For a state like Kazakhstan that is highly dependent on its production and export of raw materials, the development of oil sector plays a key role in the country's economic growth and prosperity. During the past two decades Kazakhstan was making serious decisions on formation and implementation of important projects in developing the oil industry for the country's progress. Nowadays, the Republic of Kazakhstan is getting involved in a big number of projects for purposes of oil sector development and becoming one of the international key oil suppliers. This article explains the process of oil development, its challenges in the Republic of Kazakhstan taking into account the international and domestic issues.
Қазақстан Республикасы мұнай секторының даму стратегиясы мен үдерісі
Стратегия и процессы развития нефтяного сектора Республики Казахстан
Keywords: Oil; Kazakhstan; Central Asia; independence; development; foreign investment; consortiums; economy; state-building; security; oil companies; nationalization; energy politics; Russia; China